Propuesta de diseño arquitectónico y de sitio para el sector Prusia del Parque Nacional Volcán Irazú - Cifuentes-Chacón, Ricardo (Instituto Tecnológico de Costa Rica., 2019)
The architectural and site design proposal for the Prusia sector of the Irazú Volcano National Park seeks to solve the infrastructure deficiency present in this site, by promoting a model of tourism that is sustainable and attractive to visitors. Currently the influx of tourists is very high and the existent infrastructure is not suitable for the proper management of the amount of tourists that the sector receives. The project consists of the intervention of the three main sectors of Prusia, providing them with infrastructure to host recreational, environmental and administrative activities. The proposal is based on the analysis of the site and the different types of users in order to offer activities and spaces according to the current needs and the potential of Prusia as a family-oriented tourist destination in a natural environment. The development of the proposal is based on guidelines for architecture for sustainable tourism, seeking to generate the minimum impact on the natural environment and taking advantage of the different variables it offers.
Proyecto de gradución (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, 2019.
Keywords: Diseño arquitectónico; Parques Nacionales; Turismo sostenible; Arquitectura sostenible